2000
DOI: 10.1053/euhj.1999.1872
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance affects endothelium-dependent acetylcholine-induced coronary artery response

Abstract: These results suggest that there is an association between high insulin resistance and coronary vascular endothelial cell dysfunction, and that insulin resistance may be an indicator of early stage coronary artery atherosclerosis not detectable by angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 24 publications
0
20
0
1
Order By: Relevance
“…Our observations are in accordance with previous reports showing that insulin resistance may contribute to coronary endothelial dysfunction in both animals and humans. [34][35][36][37][38][39][40][41] Characterization of the molecular mechanisms responsible for the impaired action of insulin action and the endothelialmediated vascular responses to the metabolic derangements induced by insulin resistance is of considerable clinical interest. At the cellular level, the signaling pathways of insulin-mediated glucose uptake and that of NO production are common in part.…”
Section: Discussionmentioning
confidence: 99%
“…Our observations are in accordance with previous reports showing that insulin resistance may contribute to coronary endothelial dysfunction in both animals and humans. [34][35][36][37][38][39][40][41] Characterization of the molecular mechanisms responsible for the impaired action of insulin action and the endothelialmediated vascular responses to the metabolic derangements induced by insulin resistance is of considerable clinical interest. At the cellular level, the signaling pathways of insulin-mediated glucose uptake and that of NO production are common in part.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that the endothelium-dependent response of normal coronary arteries may be blunted by IR, thereby leading to coronary vascular endothelial dysfunction [4]. Hyperinsulinemia or IR has been emphasized as a coronary risk factor [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…18,33,35,36 In particular, insulin resistance with dyslipidemia characterized by postprandial hyperlipidemia is part of the so-called metabolic syndrome, 35,36 and has been reported to be an indicator of coronary and systemic artery atherosclerosis. 37,38 RLP-C elevation after oral glucose ingestion was observed in patients with impaired glucose tolerance accompanied by insulin resistance. 39 They may be a close association of insulin resistance with postprandial RLP-C elevation in the present study population, but as we did not assess insulin resistance, the mechanism of postprandial RLP-C elevation remains uncertain.…”
Section: Fat-loading and Postprandial Hyperlipidemiamentioning
confidence: 99%